Dos fabaceas arbóreas (Erythrina amazonica Krukoff y Gliricidia sepium) con dos distanciamientos de siembra en cercos vivos en rendimiento de forraje en Zungarococha, Perú - 2019 - Cordova Arevalo, Angel (2022)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Vaccine Project in the Zungarococha Fundo, entitled TWO FABACEAS ARBOREAS WITH TWO DISTANCES OF SEEDING IN NEAR LIVING PERFORMANCE IN ZUNGAROCOCHA, PERU - 2019 The evaluations were carried out at the eighth week after planting with vegetative seed (stakes), in linear plots of 5.2 m and an experimental area of 361.24 m2. With a Randomized Complete Block Design (DBCA), with a factor of 2 x 2 with four treatments and four repetitions, the treatments under study were: T1 (Erytrhina + 0.2 x 0.2 m), T2 (Erytrhina + 0.4 x 0.4 m ), T3 (Gliricidia + 0.2 x 0.2 m) and T4 (Gliricidia + 0.4 x 0.4 m), obtaining the following results: Fabácea Gliricidia sepium, achieved the highest plant height at the 8th week of evaluation, compared to fabácea Erytrin sp. For the distancing factor, with the planting distance of 40 cm, greater plant height was achieved. In the production of green matter and dry M, no significant statistical differences were evident in the two fabaceae studied. What happens is with the planting distances, which with the smaller distance (D1 = 20 cm), increased production of green and dry matter was achieved.